Second or foreign language acquisition: experiences of Tan Sri Dr. Mohd Daud Bakar - Amani Hakim; Nik Hanan Mustapha; Mohamed Abdelrahman Ibrahim Youssef (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study deals with the aspects of second or foreign language acquisition that have become a natural phenomenon in the current era of globalization. This phenomenon is driven by several factors, including moving to other countries for certain purposes such as work, education, etc., in addition to personal factors to add and master language skills other than the mother tongue. Therefore, this study aims to describe the process of second language acquisition according to the point of view of applied linguistics, by presenting the theories related to this topic. In this qualitative study, the document analysis method has been adopted whereby the second language acquisition theories have been linked to the personal experience of the Malaysian Islamic scholar, Tan Sri Dr. Mohd. Daud Bakar. It is concluded from this study that there are many theories that form the basis for a second or foreign language acquisition, but these theories do not stand alone, rather they are interconnected with each other. Experiences of Tan Sri Dr. Mohd. Daud Bakar in learning second and foreign languages abroad serve as clear evidence for this process.